Trust Deficit in Public Institutions and the African National Congress under the Democratic Experiment: Ominous Signposts Missed? - Johannes Tsheola; Mokoko Sebola (International Journal of Social Sciences Review, 2023)
The article analyses survey and elections results from Afrobarometer and the Electoral Commission of South Africa (IEC), respectively, to demonstrate the relationship between the worsening public trust deficits in institutions of the state, constitutional democracy, and politics, on the one hand, and the ruling ANC’s declining electoral fortunes. It asserts that South Africa’s democratic experiment, under the ANC’s 28 years state governance, was placed on the precipice of civil strife; and, that the July 2021 violent public unrest, destruction of infrastructure and pillage points to ominous signposts of popular citizenry acceptance of anarchy. The article offers three concluding remarks, thus: the ruling ANC’s declining electoral fortunes will be hard to halt and reverse because whereas it is easy to lose public trust, it is hard to regain and uphold; the ANC’s conduct of the 28 years state governance has set South Africa’s democratic experiment on the precipice of ominous signposts of civil strife as societal political leadership vacuum is formed and consolidated; and, unless if the ANC reverts to undemocratic and/or fraudulent electoral conduct to stay in power, it will be decades before it recovers from the ongoing electoral slide. Finally, it recommends that the South African citizenry needs to ensure that the societal political leadership vacuum created by the erosion of public trust may not be consolidated and exploited by undemocratic forces to install unelected government.